2022
DOI: 10.3389/fpubh.2021.818614
|View full text |Cite
|
Sign up to set email alerts
|

Green Supply Chain Management With Sustainable Economic Growth by CS-ARDL Technique: Perspective to Blockchain Technology

Abstract: Logistics plays a major part in any country's or region's economic success. Logistics performance depends upon the trade between other countries and urbanization. Urbanization has major role in logistics performance. However, being a significant energy user, logistics has negative consequences. As the logistics performance increases, carbon emissions increase as well because of more transportation and urbanization. Logistics performance has positive effects related to trade openness which reduces carbon emissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 55 publications
(60 reference statements)
0
7
0
Order By: Relevance
“…ere are many differences in carbon dioxide emissions among countries and the corresponding reasons. ere are many differences in CO 2 emissions between countries, and the basis of this classification is not only based on the boundaries of tourism areas, nor is the high or low standard set by the size of CO 2 emissions, but the classification should take into account the tourism situation, the rate of tourism development and growth patterns [14,15]. e situation, the speed of tourism development, and the way of growth should be comprehensively considered.…”
Section: Basic Knowledge and Related Calculation Methodsmentioning
confidence: 99%
“…ere are many differences in carbon dioxide emissions among countries and the corresponding reasons. ere are many differences in CO 2 emissions between countries, and the basis of this classification is not only based on the boundaries of tourism areas, nor is the high or low standard set by the size of CO 2 emissions, but the classification should take into account the tourism situation, the rate of tourism development and growth patterns [14,15]. e situation, the speed of tourism development, and the way of growth should be comprehensively considered.…”
Section: Basic Knowledge and Related Calculation Methodsmentioning
confidence: 99%
“…Servant leadership (SEL) is defined as “an idea and practice of leadership that prioritizes the good among those led over through the self-interest of the leader, stressing leader behaviors that focus upon follower growth, and de-emphasizing glorify of the leader ( Tuan, 2022 ).” Servant leaders are those who lead with a concentration on the supporters, with the believers as the primary concern and organizational matters as a secondary concern ( Irving, 2011 ). The servant-leader constructions are attributes, which are described as a person’s excellent moral qualities, general decency, or moral perfection ( Gu et al, 2022 ). According to the studies related to human relations, interpersonal trust is a key component of successful and long-lasting human partnerships ( Afridi et al, 2020 ).…”
Section: Theoretical Support and Hypothesismentioning
confidence: 99%
“…Knowledge awareness is derived from personal experience and routine acts as viewed through various media. Awareness matures as a result of one's psychological process, and it corresponds to the connected emotions and experiences about a certain action (Gu et al, 2022 ). Previous research has shown that being cognizant of green practices can lead to a positive and favorable attitude about contradancing them (Sadiq et al, 2022 ).…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%